Bimanual information processing and the impact of conflict during mirror drawing - Serrien, Deborah J. (Elsevier, 2009)
Successful motor behavior depends on optimal information processing and planning. In the present study, the neural response of the motor system to conflict of visuomotor discrepancy (mirror-reversed vision) and complexity (task difficulty and hand laterality) was evaluated during the performance of bimanual actions. EEG coherence, expressing interregional communication, showed that conflict of visuomotor incongruence resulted in activation changes in both hemispheres, whereas conflict of task complexity evoked adjustments primarily in the left hemisphere. Furthermore, interhemispheric coherence was modified due to both forms of conflict. This demonstrates that conflict demands elicit distinct processes across the motor system. The data further illustrate that functional couplings are dynamically modulated during bimanual behaviour, suggesting that interactions between brain regions provide higher-order links for information processing and integration in view of complex motor skills.